Mutated primer binding sites interacting with different tRNAs allow efficient murine leukemia virus replication. - Lund, A H (1993)
Two Akv murine leukemia virus-based retroviral vectors with primer binding sites matching tRNA(Gln-1) and tRNA(Lys-3) were constructed. The transduction efficiency of these mutated vectors was found to be comparable to that of a vector carrying the wild-type primer binding site matching tRNA(Pro). Polymerase chain reaction amplification and sequence analysis of transduced proviruses confirmed the transfer of vectors with mutated primer binding sites and further showed that tRNA(Gln-2) may act efficiently in conjunction with the tRNA(Gln-1) primer binding site. We conclude that murine leukemia virus can replicate by using various tRNA molecules as primers and propose primer binding site-tRNA primer interactions to be of major importance for tRNA primer selection. However, efficient primer selection does not require perfect Watson-Crick base pairing at all 18 positions of the primer binding site.